Persistent opioid use in patients with multiple myeloma post‐ASCT. (28th February 2022) - Danish, Matthew L.; Shah, Mansi R.; Lin, Yong; Ho, Joseph K.; Copeland, Tabitha M.; Cooper, Dennis L.
Abstract: Purpose: Bone pain is a common presenting symptom of multiple myeloma (MM) and is frequently treated with opioids in addition to myeloma directed therapy. With improved response and survival with modern myeloma therapy, it is important to re‐examine the role of opioids in managing symptomatic myeloma. Patients and Methods: We performed a retrospective analysis of patients with myeloma at Rutgers Cancer Institute of New Jersey (RCINJ) who received an ASCT between January 1, 2012, and December 30, 2017, and who had subsequent follow‐up (a total of 138 patients). We sought information specifically from the visits after induction therapy but prior to ASCT, at 100 days and 1‐year post‐ASCT follow‐up visits. We compared opioid users and non‐users in relation to treatment response, co‐morbid conditions, and symptoms. We also examined amounts, duration, and odds of continued opioid use. Results: At the time of the first analysis (before transplant), 34.8% of patients were using opioids and opioid use was more frequent in younger patients and, as expected, in patients with bone lesions. At 1 year, 31.9% of patients were still using opioids and continued opioid use was not correlated with disease response. Of the patients using opioids at the time of transplant, 58% either maintained their opioid dose or increased it at 1‐year post‐transplant. Conclusions: This retrospective analysis shows that despite a small decrease in opioid use over time, opioid use remains frequent in MM patients and is correlated with younger age and bone involvement but not with response to therapy. Over half the patients using opioids at the time of transplant continued or increased opioid use over the following year. With increasing survival in myeloma patients, further attention is required to distinguish cancer pain from chronic pain in cancer patients.